Aesthetics of Artistic Formation in Mahdi Naseer's Poetry - Al-Bzour, Ahmad Mohammad (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aims to reveal the components of the poetic textual form, and its artistic and aesthetic elements of the Jordanian poet Mahdi Naseer, in order to analyze, interpret, and correct it, according to the requirements of productive artistic aesthetic reading. Methods: The selection fell on poetic texts from multiple collections, namely: legends, a hundred hymns to their raging moons, the transformations of Abu Raghal, a reading in a desert inscription, Thamudic rhythms, and a stone woman. The study tried to memorize the aesthetic features in expression, using the artistic approach, starting from the structure of the phrase, to distinguish the language of the poetic text of Mahdi Naseer from the cases of ordinary daily linguistic performance and The familiar, and discussing the linguistic role in crystallizing the aesthetic expression. Results: Mahdi Naseer makes his poetic text governed by beauty, directing the textual form to the circle of tyranny of artistic formulation from the possibilities of language. As a conclusion, the poet's relationship with the language is a relationship based on the destruction of the familiar formulation imposed on the language, and he was able to present poetic texts, characterized by the form Stereoscopic, woven with apparent care, and selected words. Conclusions: The poet Mahdi Naseer has a distinguished linguistic and stylistic feature in the choice of words. He adapted the language, not as a means of communication, as much as it represents a goal for him; To achieve an aesthetic end, the aesthetic use of language has been extended in many of his poetic texts.